2016
DOI: 10.1002/app.44548
|View full text |Cite
|
Sign up to set email alerts
|

In situ formed internal water channels improving water swelling and mechanical properties of water swellable rubber composites

Abstract: In this study, electrospun nanofibers of poly (vinyl alcohol) (PVA) and styrene-butadiene-styrene triblock copolymer (SBS) were employed in conventional water-swellable rubber (WSR) to design WSR composites with improved water swelling and mechanical properties. With the introduction of PVA nanofibers, considerable improvement in elasticity, strength, and water-swelling behavior was observed. After immersion, PVA nanofibers dissolved within the composite to in situ form water channels to connect isolated super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The SANs at 110 °C presented larger absorption areas than the SANs at 130 °C because they were dissolved by water rather than absorbing it, as shown in Figs (a) and (b). Moreover, the rate of increase in area displayed irregular trends because of the random formation of channels for transferring water within the nanoweb when the SANs at 110 °C were dissolved . As SAP was produced in the nanofibers, the highly porous structure efficiently spread water through the nanofibers with additional capillary force.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SANs at 110 °C presented larger absorption areas than the SANs at 130 °C because they were dissolved by water rather than absorbing it, as shown in Figs (a) and (b). Moreover, the rate of increase in area displayed irregular trends because of the random formation of channels for transferring water within the nanoweb when the SANs at 110 °C were dissolved . As SAP was produced in the nanofibers, the highly porous structure efficiently spread water through the nanofibers with additional capillary force.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the fabrication of superabsorbent nanofibers (SANs) has been widely attempted because of the advantages that nanofibers offer, such as a high surface area and a porous structure . However, most previous studies produced SANs by simply adding nanofibers to SAP substrates or by adding SAP particles to polymer nanofiber structures that requires an additional process.…”
Section: Introductionmentioning
confidence: 99%
“…Base materials can be made up of metals, polymers, glass, or composites. Moreover, hydrogels as a swell able polymer with enviro-sensitive properties are having a profound impact in a broad range of applications due to their exceptional physicochemical, mechanical, electrical, and optical properties [ 3 , 4 , 5 ]. Despite the period since their initial discovery in 1968, hydrogels have emerged as a promising platform with surprising and enormous potential for biomedical use.…”
Section: Introductionmentioning
confidence: 99%
“…A highly crystallized PVA hydrogel has low swelling property, making it desirable for specific biomedical and pharmaceutical applications [4][5][6]. Different studies have shown the notable performance of PVA hydrogel and its composites for wound healing [7], sensors and electrodes [8,9], tissue engineering [10][11][12] and biomedical applications [13][14][15].…”
Section: Introductionmentioning
confidence: 99%